2013
DOI: 10.1111/cen.12124
|View full text |Cite
|
Sign up to set email alerts
|

Does hypopituitarism recover when macroprolactinomas are treated with cabergoline?

Abstract: In our study, in a group of patients with macroprolactinoma systematically assessed at intervals, pituitary dysfunction in response to cabergoline was found to be mostly irreversible, except for the gonadotroph axis which showed restoration in a subset of subjects following achievement of normoprolactinaemia. It would appear that the reversibility of pituitary axes may be less common than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The data regarding other pituitary hormones is less consistent. We found some recovery of the corticotrophs with no thyrotroph recovery [55], Colao et al [30], found similar patterns, Karavitaki et al [21] showed recovery of thyrotrophs in 25 % of affected patients but no recovery of ACTH secretion and Sibal et al [35] demonstrated re-secretion of both ACTH and TSH in some patients in their cohort.…”
Section: Reviewsupporting
confidence: 67%
See 2 more Smart Citations
“…The data regarding other pituitary hormones is less consistent. We found some recovery of the corticotrophs with no thyrotroph recovery [55], Colao et al [30], found similar patterns, Karavitaki et al [21] showed recovery of thyrotrophs in 25 % of affected patients but no recovery of ACTH secretion and Sibal et al [35] demonstrated re-secretion of both ACTH and TSH in some patients in their cohort.…”
Section: Reviewsupporting
confidence: 67%
“…However, in some patients shrinkage may become noticeable after only 6 months of therapy [31]. Most of the studies (8/11) verified adenoma shrinkage in response to CAB in all [1821, 23, 24], or almost all [17, 26] patients, totaling 86.6 % of treated patients (see Table 1). …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, few patients had central hypocortisolism and central hypothyroidism at presentation, hence gender difference in this regard could not be commented upon. Reported hypopituitarism (other than hypogonadism) in prolactinomas is based on data derived from small number of patients and with nonidentical diagnostic criteria leading to variable conclusions (10) . We have used 0800 h serum cortisol to define hypocortisolism, due to nonavailability of adrenocorticotrophic hormone (ACTH) pharmaceutical preparation in India.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of prolactinomas relate to mass-effects (most frequently visual field defects, headaches and hypopituitarism) and/or to hyperprolactinemiarelated consequences (hypogonadism and its sequelae and galactorrhea). Primary goals of treatment are reduction in tumor size, achievement of normal prolactin and restoration of gonadal function [7,8]. The treatment of prolactinomas is unique amongst the PitNETs, since they are the only type of pituitary tumor in which first-line approach is medical therapy [with dopamine agonists (DA)] rather than surgery.…”
Section: Introductionmentioning
confidence: 99%